Symptomatological and cognitive correlates of vascular comorbidity in older-elderly (at least 75 years old) men with major depressive disorder - Yu-Yuan Wang; Yun-Hsuan Chang; Sheng-Yu Lee; Chih-Chun Huang; I-Hui Lee; Tzung-Lieh Yeh; Yen-Kuang Yang; Yan-Chiou Ku; Ru-Band Lu (Kaohsiung Journal of Medical Sciences, 2012)
Depression is a common geriatric psychiatric disorder increasing with age among elderly people (≥ 75 years old), especially those with medical comorbidities. They have higher suicide rates than younger men, but these are paid less attention. Elderly men (n=141) who were newly admitted residents of the Veterans' Home in Tainan, Taiwan from 2004 to 2006 were recruited and screened for major depression. Specialist physicians obtained past histories of medical illnesses through chart reviews, interview, and health examinations. Fifty-nine of the 141 elderly people had major depression and participated in this study. Thirty-nine men in the group with vascular comorbidities (VC), and 20 in the group without (NVC) vascular comorbidities were compared. The VC group had more time-orientation impairment, greater psychomotor retardation, and diminished concentration/decision-making than did the NVC group. Psychomotor retardation and other cognitive function impairments (e.g., concentration and decision-making) are characteristic manifestations among patients with major depression and vascular comorbidity compared with those without vascular comorbidity.